Spinal cord injury and inflammatory mediators: Role in “fire barrier” formation and potential for neural regeneration - Mi Zhou; Zhengyu Xu; Hao Zhong; Guangzhi Ning; Shiqing Feng (Neural Regeneration Research)
Traumatic spinal cord injury result in considerable and lasting functional impairments, triggering complex inflammatory and pathological events. Spinal cord scars, often metaphorically referred to as “fire barriers,” aim to control the spread of neuroinflammation during the acute phase but later hinder axon regeneration in later stages. Recent studies have enhanced our understanding of immunomodulation, revealing that injury-associated inflammation involves various cell types and molecules with positive and negative effects. This review employs bibliometric analysis to examine the literature on inflammatory mediators in spinal cord injury, highlighting recent research and providing a comprehensive overview of the current state of research and the latest advances in studies on neuroinflammation related to spinal cord injury. We summarize the immune and inflammatory responses at different stages of spinal cord injury, offering crucial insights for future research. Additionally, we review repair strategies based on inflammatory mediators for the injured spinal cord. Finally, this review discusses the current status and future directions of translational research focused on immune-targeting strategies, including pharmaceuticals, biomedical engineering, and gene therapy. The development of a combined, precise, and multitemporal strategy for the repair of injured spinal cords represents a promising direction for future research.